A Fe–Ga alloy cantilever film vibration harvester with a double-stage signal processing circuit and its main performance testing. (November 2019) - Liu, Huifang; Wei, Linru; Liang, Quan; Cao, ChongDong; Ma, Kai; Gao, Shuang; Cong, Chen
Abstract: With the power consumption of sensor nodes and wireless communication system have been significantly reduced from mW to μW, a new and interesting research field emerges, which is, the power generation technology through harvesting vibration energy from ambient vibration. It might represent a new way to overcome the unsatisfactory battery issue in low-power electronic devices. The aim of this study is on outlining, the basic behavior of a Fe87 Ga13 based cantilever harvesting systems. Based on the previous research results in this field, we proposed a cantilever film vibration harvester using Fe–Ga alloy and a double-stage signal processing interface circuit. It was a composite beam structure as a whole in which the Fe–Ga alloy layer and basal layer were closely wound with a pickup coil of wire. The coupling correlation relationship of multi-fields, including mechanical, magnetic and electrical, occurring in the harvester, were analyzed utilizing a distributed-parameter model. Experimental testing were conducted to thoroughly research the main working performance of the harvester which was under the base excitation or transient free excitation, and the main working performances of Fe–Ga alloy based cantilever harvester were obtained clearly. The DC output from the double-stage interface circuit reached to 17.7 V which was far greater than 1.6 V only amplified through a voltage quadrupler rectifier circuit. The prototype succeeded to keep lighting up multi-LEDs, which validated the power generation capability of the prototype and the feasibility of the interface circuit and allowed us to imagine such harvester to supply LED indicators, wireless sensor nodes and other devices with low power consumption.